2011
DOI: 10.1177/1740349912436450
|View full text |Cite
|
Sign up to set email alerts
|

Facile control synthesis of Ag3PO4 and morphologies effects on their photocatalytic properties

Abstract: We reported that Ag 3 PO 4 exhibits excellent photocatalytic properties for organic dye decomposition under visible-light irradiation. Herein, studies of photocatalytic performance have indicated that nano rhombic dodecahedrons (S1) exhibit much higher activities than micro rhombic dodecahedrons (S3) for the degradation of organic contaminants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…[1,2] As the formation of electron/hole pairs on the surface of APO particles plays an important role in the photocatalytic performance, many studies have been carried out with the aim to control the particle size or particle morphology to increase the specific surface area. [3][4][5][6] The studies showed that synthesis parameters such as the precipitating agents, [7,8] the ratios of the starting materials, [9,10] the concentration of the reaction catalysts, [5,11] the fabrication time, [3,4,12] and pH conditions [13] greatly influence the size and morphology of the particles.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] As the formation of electron/hole pairs on the surface of APO particles plays an important role in the photocatalytic performance, many studies have been carried out with the aim to control the particle size or particle morphology to increase the specific surface area. [3][4][5][6] The studies showed that synthesis parameters such as the precipitating agents, [7,8] the ratios of the starting materials, [9,10] the concentration of the reaction catalysts, [5,11] the fabrication time, [3,4,12] and pH conditions [13] greatly influence the size and morphology of the particles.…”
Section: Introductionmentioning
confidence: 99%